2021
DOI: 10.1080/09537325.2021.1947490
|View full text |Cite
|
Sign up to set email alerts
|

How R&D cooperation, R&D expenditures, public funds and R&D intensity affect green innovation?

Abstract: Green innovation plays a substantial role in creating new products and services, as well as in reducing environmental impacts and promoting the efficient use of resources and materials. This study investigates the linkage between green innovation and research and development (R&D) practices inside and outside firms over time; it also explores types of external partners. The results show that internal and external R&D efforts enhance the activities of green innovation. However, the external partner is an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 56 publications
0
34
0
1
Order By: Relevance
“…Appropriate funding and resources to implement green innovation greatly contribute to the success of this type of innovation (Miao et al. , 2021; Sánchez-Sellero and Bataineh, 2022).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate funding and resources to implement green innovation greatly contribute to the success of this type of innovation (Miao et al. , 2021; Sánchez-Sellero and Bataineh, 2022).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The high technological intensity that is often present in large manufacturing firms plays a role in generating green innovations through increased spending on research and development, which helps these firms overcome the difficulties that firms may face during the innovation process(Galliano and Nadel, 2015). Appropriate funding and resources to implement green innovation greatly contribute to the success of this type of innovation(Miao et al, 2021;S anchez-Sellero and Bataineh, 2022).…”
mentioning
confidence: 99%
“…Yu Bai (2021) used big data samples from 503 enterprises to construct a multirelationship network and found that the breadth and depth of the relationship networks of enterprises are positively correlated with green innovation [77]. Sánchez-Sellero (2021), using data from the Spanish Technological Innovation Panel, found that establishing R&D cooperation with external partners is the key driving force to promote the green innovation of enterprises [83].…”
Section: Board Size and Green Innovationmentioning
confidence: 99%
“…On the other hand, R&D talents have the characteristics of wide regional distribution and high industry penetration density. Increasing the input of R&D personnel can give full play to the knowledge spillover effect, that is, through the communication between R&D personnel, the innovation output can be highly efficient (Sánchez-Sellero and Bataineh, 2021 ). In addition, the input of R&D funds is the basic guarantee of green innovation output (Bai et al, 2019 ), and it is the prerequisite for purchasing production equipment and recruiting high-tech talents.…”
Section: Research Hypothesis and Empirical Designmentioning
confidence: 99%